The Concept Of Learning Evaluation In The Perspective Of Tafseer Tarbawy - Wahidi, Rosid; Abdussalam, Aam; Surahman, Cucu (PT. Student Rihlah Indonesia, 2025)
This researchThe Concept of Learning Evaluation in the Perspective of Tafsir Tarbawi is an important study to conduct, as it is a mandatory component of educational activities and serves measure of the success of learning processes. Purpose of this research is to describe problems in the evaluation system as an educational component, explain concept of evaluation from the perspective of tafsir tarbawi, and outline procedures for organizing evaluations in educational institutions. This study employs qualitative approach with literature study method. Results and discussion reveal several issues in the implementation of evaluation systems, including indications of manipulation in reporting minimum competency scores, low synergy between teachers and parents, and suboptimal school work programs. Moreover, evaluation in the perspective of tafsir tarbawi encompasses several aspects, such as the meaning of evaluation, its objectives, functions, principles, and systems. Moreever, the procedures for organizing evaluations in educational institutions include planning, conducting assessments, monitoring, data processing, reporting, and utilizing evaluation results.